Evaluation of movement and physiological demands of full-back and center-back soccer players using global positioning systems - Molinos Domene, A. (Journal of Human Sport & Exercise, 2013)
Purpose: This study investigated the physiological demands between Full-back and Center-Back soccer players during official matches and using Global Positioning System (GPS) devices. Methods: Four Full-back (FB) and four Center-back (CB) semi-professional soccer players (mean ± SD age 21,33 ± 2.07 y, height 179.53 ± 4,37 cm, and weight 76.62 ± 3.32 Kg) participated in this study during 2012. Match performance was reported as total distance, speed categories (stationary-walking (0-3.9 km/h), jogging (4.0-6.9 km/h), quick running (7.0-12.9 km/h), high-intensity running (13.0-17.9 km/h) and sprint (>18 km/h)), maximum speed, workload, high-intensity running distance (HIR: Sprint and High-intensity running), rest time and high/low intensity ratio. Data were expressed per 15-min period of game time, separate into positions roles. Results: in all periods of time, FB covered a significant higher total distance, HIR efforts, Workload and maximum speed. CB spent higher distance in walking speed category. FB had also a lower high/low ratio and shorter rest time. When compared with periods of time, rest time was longer each 15-min, but in the last period (75-90) HIR was higher than in the previous periods of time. Conclusions: Significant differences exist between Full-back and Center-back players, therefore, physical training in soccer should also be based on the specific requirements of the playing positions.